2018
DOI: 10.1007/s10552-018-1041-0
|View full text |Cite
|
Sign up to set email alerts
|

A pilot study of prostate cancer knowledge among African American men and their health care advocates: implications for screening decisions

Abstract: Health care advocates of the 33 male participants were usually women, spouses, or significant others, supporting the vital role women play in men's health specifically in rural underserved communities. Low overall PCa knowledge, including their risk for PCa, among these participants indicates a need for PCa and screening educational interventions and dialogue that include males and their significant others.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 19 publications
0
15
0
Order By: Relevance
“…Knowledge about prostate cancer risk, as determined by a composite measure, was found to be low. This was confirmed by both Consedine et al 26 and Oliver et al 27 Consedine surveyed 180 U.S.‐born African American, U.S.‐born White, and immigrant Jamaican men, who reported poorer knowledge of prostate cancer than White men. Oliver et al 27 reported that prostate cancer knowledge was somewhat low, with individuals correctly answering approximately 6 questions out of 10 at multiple time points.…”
Section: Resultsmentioning
confidence: 66%
“…Knowledge about prostate cancer risk, as determined by a composite measure, was found to be low. This was confirmed by both Consedine et al 26 and Oliver et al 27 Consedine surveyed 180 U.S.‐born African American, U.S.‐born White, and immigrant Jamaican men, who reported poorer knowledge of prostate cancer than White men. Oliver et al 27 reported that prostate cancer knowledge was somewhat low, with individuals correctly answering approximately 6 questions out of 10 at multiple time points.…”
Section: Resultsmentioning
confidence: 66%
“…The issue with using shared decision-making to receive a prostate cancer screening is that it requires men to be educated and willing to communicate about prostate cancer. Researchers observed that Black men were unaware of their increased risk for prostate cancer and had poor knowledge about the disease (Gwede et al, 2015;Jones et al, 2009;Lepore et al, 2017;Mofolo et al, 2015;Oliver et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Unfortunately, the medical literature consistently supports the concerning reality that African American men are insufficiently screened for both BPH and prostate cancer [29]. Consistent with other healthcare issues, African American men are more likely to be disproportionately impacted by insufficient healthcare literacy [30][31][32]. Interestingly, previous studies have shown that black men are more likely to report a lower bother score relative to white populations with similar LUTS severity [33].…”
Section: Screening Literacy and Community Interventionmentioning
confidence: 99%
“…It contains seven questions related to BPH symptoms and one question related to the patient's perceived quality of life. BPH symptom severity is proportionate to the IPSS score, which ranges from 0 to 35 and categorizes symptoms as mild (1-7), moderate (8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19), or severe (20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35). The IPSS survey is widely used in Urology and the AUA also encourages its use in primary care settings.…”
Section: Screening Literacy and Community Interventionmentioning
confidence: 99%
See 1 more Smart Citation